Sclerosing Epithelioid Fibrosarcoma of the Thoracic Vertebrae: An Fairly Unusual Case Report With a Short Review of Literature - Wei, Changhong; Ma, Yili; Wu, Dengqiang; Chen, Xiaoyu; Li, Chunjun; Chen, Jun; Zhou, Sufang (Frontiers in Medicine, 2022)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare subtype of soft tissue tumors, and SEF originating from the side of the spine is even rarer. We report that a 28-year-old young woman suffered from chest pain and back pain for three years, and thereafter she went to see a doctor because her condition deteriorated. Enhanced CT showed that the right posterior upper chest wall mass invaded the adjacent bone, and the boundary between the lesion and the surrounding tissues was relatively clear. She then underwent posterior tumor removal surgery. The pathological examination confirmed the diagnosis of SEF. In histomorphology, the tumor displayed a typical epithelioid clear cell morphology, accompanied by extensive vitrification and fibrosis, which significantly improved the differential diagnosis of low-grade fibromyxosarcoma, solitary fibroma, and other tumors. The immunohistochemical analysis showed a diffuse positive reaction to MUC4, a highly specific marker of SEF, which was detected by fluorescence in-situ hybridization (FISH), and confirmed that the EWSR1 gene was rearranged, while the FUS gene was not rearranged. This is the first time that we have encountered such variations and thus report this rare case with updated literature related to this tumor.